Pengelolaan Badan Usaha Milik Desa di Desa Batuhideung Kecamatan Cimanggu Kabupaten Pandeglang Berdasarkan Peraturan Bupati Pandeglang Nomor 27 Tahun 2016 Tentang Tata Cara Pendirian Dan Pengelolaan Badan Usaha Milik Desa - Saepudin Saepuidn (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
Village Owned Enterprises are business entities whose entire or most of the capital is owned by the Village through direct participation originating from Village assets which are separated in the context of asset management, services and other businesses for the welfare of the Village community. BUMDesa Berkarya requires special attention from the village government, especially in coaching, development and supervision. Although there is already a more specific legal umbrella that regulates BUMDes as stated in the Pandeglang Regent Regulation Number 27 of 2016 concerning Procedures for Establishing and Managing Village-Owned Enterprises, BUMDesa Berkarya still has many obstacles, both internal and external. The absence of innovation and the lack of human resources are the main obstacles for BUMDes to develop. The author conducts thesis research using two problem identifications. First, how is the management of BUMDes in Batuhideung Village, Cimanggu District, Pandeglang Regency?. Second, what are the obstacles faced in the management of BUMDes in Batuhideung Village, Cimanggu District, Pandeglang Regency?. The theory used in this study uses Authority Theory and Welfare Theory. The method used in this thesis research is empirical juridical. The research specification uses descriptive analysis. The results showed that in the management of Village Owned Enterprises Berkarya in Batuhideung Village, Cimanggu District, Pandeglang Regency in accordance with existing mechanisms and in accordance with Pandeglang Regent Regulation Number 27 of 2016 concerning Procedures for Establishing and Managing Village-Owned Enterprises however, in its implementation there are many obstacles and obstacles so that BUMDesa Berkarya has not been able to become a business entity that fully accommodates the potential that exists in the village. Suggestions for building BUMDes Berkarya are to coordinate intensively with the local government, make efforts to develop types of businesses that are in accordance with the potential that exists in the village and carry out innovations that are beneficial to the village community.